2006
DOI: 10.1038/sj.bjp.0706908
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses to combined treatment with selective monoamine oxidase type B inhibitors and L‐DOPA in the rat

Abstract: Background and purpose: Postural hypotension is a common side-effect of L-DOPA treatment of Parkinson's disease, and may be potentiated when L-DOPA is combined with selegiline, a selective inhibitor of monoamine oxidase B (MAO-B). Rasagiline is a new, potent and selective MAO-B inhibitor, which does not possess the sympathomimetic effects of selegiline. We have studied the effects of these selective MAO inhibitors, L-DOPA and dopamine on the cardiovascular system of the rat. Experimental approach: Blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…This is in agreement with earlier findings in rats and cats (Finberg et al, 1981; Chen and Swope, 2005; Finberg et al, 2006). …”
Section: Indications In Parkinson's Diseasesupporting
confidence: 94%
See 1 more Smart Citation
“…This is in agreement with earlier findings in rats and cats (Finberg et al, 1981; Chen and Swope, 2005; Finberg et al, 2006). …”
Section: Indications In Parkinson's Diseasesupporting
confidence: 94%
“…The main metabolite of rasagiline is aminoindan. Therefore any cardiovascular responses of rasagiline are neglectible as shown in animal studies ( Finberg et al, 2006 ) and in all clinical trials including the TEMPO- ( Parkinson Study Group, 2002 ), PRESTO- ( Parkinson Study Group, 2005 ), LARGO- ( Rascol et al, 2005 ) and ADAGIO-study ( Olanow et al, 2008 ; 2009 ).…”
Section: Indications In Parkinson's Diseasementioning
confidence: 99%
“…48 Although MAO-AIs enhance extracellular levels of dopamine produced from L-dopa, irreversible, and selective MAO-AI cannot be used in the PD therapy, because of cardiovascular side effects. 49 Another disadvantage of an irreversible MAO-AI is the hypertensive "cheese effect", 50 due to the predominance of MAO-A in the gut wall to metabolize tyramine in fermented foods such as cheese and beer. Hypertensive crises may be prevented by using reversible rather than irreversible MAO-AI, or tissue-specific inhibitors such as the brain-selective ladostigil.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that amphetamine-like drugs, such as SEL and its major metabolites, L-methamphetamine and L-amphetamine, cause tachycardia [35] , [36] , hypotension [37] , [38] or hypertension [39] . Allard et al report that 3 mg/kg of SEL induces only a transient decrease in blood pressure, which returns to its baseline value after 4 min [40] .…”
Section: Discussionmentioning
confidence: 99%